1999
DOI: 10.1007/s002329900477
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Vacuolar Ion Channels by Polyamines

Abstract: In this work, direct effects of cytosolic polyamines on the two principle vacuolar ion channels were studied by means of patch-clamp technique. Fast and slow activating vacuolar channels were analyzed on membrane patches isolated from vacuoles of the red beet taproot. The potency of the fast and of the slow vacuolar channel blockage by polyamines decreased with a decrease of the polycation charge, spermine4+ > spermidine3+ > putrescine2+. In contrast to the inhibition of the fast vacuolar channel, the blockage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
60
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 39 publications
7
60
0
1
Order By: Relevance
“…spermidine 31 putrescine 21). Similar to our results, previous studies also showed that polyamines blocked the slow-and fast-activating vacuolar cation channel in a charge-dependent manner Brü ggemann et al, 1998;Dobrovinskaya et al, 1999). These results suggested that polyamines may modulate ion channel activities through direct binding to the channel proteins.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…spermidine 31 putrescine 21). Similar to our results, previous studies also showed that polyamines blocked the slow-and fast-activating vacuolar cation channel in a charge-dependent manner Brü ggemann et al, 1998;Dobrovinskaya et al, 1999). These results suggested that polyamines may modulate ion channel activities through direct binding to the channel proteins.…”
Section: Discussionsupporting
confidence: 81%
“…9, B and C), suggesting the recirculation of K 1 from shoots to roots was decreased. Similar to our results, polyamines were well characterized as potent blockers of inward K 1 channels in both plant cells (Brü ggemann et al, 1998; Dobrovinskaya et al, 1999;Liu et al, 2000) and mammalian cells (Shin and Lu, 2005). Thus, by regulating inward and outward K 1 currents at different mode, spermidine prevented K 1 loss from shoots.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Thus, it appears that SV and FV currents make nearly equal contributions toward Na + flux across the tonoplast, and the total channelmediated current is fairly comparable to the current generated by the whole vacuolar population of H + pumps (Hedrich et al, 1988). However, as commented above, tonoplast channel activity is under the control of numerous second messengers and, as such, may be significantly up-or down-regulated in planta (Brüggemann et al, 1998;Carpaneto et al, 1999;Dobrovinskaya et al, 1999;Hedrich and Marten, 2011;Gutla et al, 2012). This may change the balance between the relative contribution of SV and FV channels toward tonoplast Na + fluxes under natural conditions.…”
Section: Influx Under Physiological Conditionsmentioning
confidence: 98%
“…In animal cells, PAs block a variety of K + and other cation-selective channels (Drouin and Hermann, 1994;Ficker et al, 1994;Lopatin et al, 1994;Bähring et al, 1997;Lu and Ding, 1999). In plants, PAs inhibit PM Shaker-type K + channels in guard, cortical, epidermal, and xylem parenchyma cells (Liu et al, 2000;Zhao et al, 2007), nonselective cation channels in mesophyll and root PM Zhao et al, 2007), as well as nonselective cation fast and slow vacuolar channels (Brü ggemann et al, 1998;Dobrovinskaya et al, 1999aDobrovinskaya et al, , 1999b. PAs are the only organic polycations that are present in sufficient quantities under stress to play the role of channels blockers without compromising cell metabolism (Alcázar et al, 2010).…”
mentioning
confidence: 99%